PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE TWO STAY TWO STRAY PADA MATERI MANFAAT ENERGI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 31 PIDIE - Abdul Manaf; Syarifah Rahmi (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to determine the application of the cooperative learning model Type Two Stay Two Stray in the material benefits of energy can improve student learning outcomes of 4th grade in MIN 31 Pidie. This type of research is classroom action research. With a KKM score of 70 for science subjects. The results of class action research cycle I obtained an average score of 63.00. In cycle II, the average value was 71.6. And in cycle III obtained an average value of 87. The completeness of student learning outcomes in cycle I which he assessed was above the KKM there were 5 students with a percentage of 25%. In cycle II, where the score is above the KKM, there are 10 students with a percentage of 50%. And in cycle III, where the score is above the KKM, there are 20 students with a percentage of 100%.